Refleksioner over forholdet mellem proces og værk: Revolution - et gør-det-selv oprør! - Malling Lykke Skov, Rasmus (Peripeti, 2021)
This text is a practice-based reflection upon the relation between the artistic process and the finished work. The starting point is the devised production ”Revolution - a do-it-yourself rebellion!” by Teater Fluks. The piece revolves around the theme of revolution, with a high degree of audience-involvement, examples from historic revolutions, abstractions and video work. We reflect upon the process through a number of fragments and subjects such as: The anatomy of the process, how to describe a project before the work is there, how we work with research, different logics of method, how to take decisions, and last but not least, the work in relation to the market, the theatre landscape and the audience.